Development of Mobile Application for Smart Flood Warning System - Lee, Jia Rock; Mohd Fadly Abd Razak (Progress in Engineering Application and Technology, 2024)
To overcome the escalating flood events globally, a flood management and early warning systems has become a necessity. This project addresses these challenges by developing a mobile application for Smart Flood Warning System, offering real-time flood data visualization, predictive analytics, and proactive alerting mechanisms. The system is integrated with advanced sensors for continuous data collection on water levels, rainfall, and flow rates, processed via sophisticated algorithms for flood monitoring. A user-centric dashboard and hotspot area on map fragment empowers users to identify flood hotspots and take timely response action to flood events. The project aims to enhance community preparedness by enabling timely alerts via SMS channels to residents in flood-prone areas. Rigorous testing and validation in real-world scenarios ensure system reliability and responsiveness. The anticipated outcomes include an accessible dashboard, an automation warning system, and increased community resilience through informed decision-making. Ultimately, this Smart Flood Warning System represents a pivotal step in fortifying flood management globally, safeguarding lives, and minimizing the impact of recurrent flood events.